Implementation of PSAK 71 In Indonesia: Mutual Fund Investment In Insurance Subsector Companies - Andy Kurniawan; Amrie Firmansyah (Jambura Equilibrium Journal, 2021)
Changes in financial accounting standards in Indonesia can result in additional costs that companies, including financial companies, must bear. This study aims to review the implementation of PSAK 71 in insurance companies in Indonesia related to mutual fund investment ownership. The method used in this study is a qualitative method with content analysis. The analysis was conducted with data and information on the financial statements for 2020 and 2019 of insurance sub-sector companies available on www.idx.co.id. A sampling of this study employed purposive sampling with a total sample that amounted to 26 observations. This study concludes that the implementation of PSAK 71 does not affect the measurement and value of mutual fund investments. It only has an impact on the classification of mutual fund investments in the company's financial statements. Also, this study finds that 4 out of 13 insurance companies have implemented a mutual fund investment classification according to PSAK 71 (2017). Insurance companies that have not implemented PSAK 71 (2017) are due to the company's policy that stipulates to apply PSAK 62 (2017), which allows insurance companies to postpone the implementation of PSAK 71 (2017).